Physical and technical attributes associated with on-water rowing performance in junior and elite rowers - Legge, N.; Slattery, D. K.; O`Meara, D. D.; McCleave, D. E.; Young, D.; Crichton, S.; Watsford, P. M. (Journal of Sports Sciences, 2024)
On-water rowing performance consists of the integration of physical and technical attributes. This exploratory study aimed to describe key physical and technical variables for elite and junior rowers and examine the associations and predictive capacity of these variables with on-water rowing performance outcomes. Twenty-eight junior (16 females, 16 ± 0.8 years and 12 males, 17 ± 0.7 years) and 24 elite rowers (12 females, 24 ± 2.7 years and 12 males, 27 ± 2.6 years) completed an on-water, single sculling biomechanics assessment combined with a series of physical, strength and power tests. Elite men and women were superior in mean gate force, distance per stroke and recovery distance compared to junior groups as determined by independent t-tests and effect size appraisal (p < 0.017, d > 1.2). Large associations (p < 0.01) were evident between anthropometry, strength and power assessments with the on-water measures of catch angle, mean gate force, recovery distance and boat speed. Differences in ROM and flexibility attributes did not distinguish between elite and junior rowers. Linear discriminant analysis revealed that individual rowers can be appropriately categorised by sex and performance level based on their physical and technical attributes. This battery of testing with world-class athletes represents an excellent level of ecological validity for the assessment of rowers pertinent to on-water performance.